37 Improving the Management of Post-Operative Hypocalcaemia in Thyroid Surgery. (4th May 2021) - Collins, R; Lafford, G; Ferris, R; Turner, J; Tassone, P
Abstract: Introduction: Hypocalcaemia is a frequent, and potentially dangerous, complication of total thyroidectomy [1, 2]. This quality improvement (QI) project was undertaken in a large ENT department in the East of England over a year. The project improved postoperative guideline compliance by optimising the recognition and management of patients at risk of hypocalcaemia. This process focussed on improving parathyroid hormone (PTH) and calcium blood testing, appropriate prescribing and the monitoring and management of hypocalcaemia. Method: Following a baseline audit the QI process subsequently involved the introduction of a new intraoperative PTH pathway and the amendment of trust guidelines. In addition, there was a focus on improving clinician awareness of guidelines, junior doctor education, communication between operating surgeons and junior doctors and the optimisation of patient handover. Results: The measurement of PTH at four hours improved from 42.5% to 52.2%. The project saw a significant improvement in the monitoring of hypocalcaemia (from 22.2% to 83.3% for patients with an intermediate risk of hypocalcaemia) and in the prescribing of prophylactic calcium supplements from 7.5% to 43.5%. Conclusions: By optimising postoperative care this QI project improved patient safety as well as impacting on the duration, and overall cost, of inpatient stay.